Double-sided laser beam welded T-joints for aluminum-lithium alloy aircraft fuselage panels: Effects of filler elements on microstructure and mechanical properties. (1st August 2017) - Han, Bing; Tao, Wang; Chen, Yanbin; Li, Hao
Graphical abstract: Highlights: Hot cracks are found on double-sided LBW Al-Li T-joints even using high Si wire. Fracture features of Al-Li T-joint are affected by non-dendritic equiaxed zone. A new Al-6.2%Cu-5.4%Si wire can promote intergranular T phase instead of T2 phase. T and T2 phase show different effects and features on hot crack propagation. By new wire, cracks are inhibited by bridging of rich secondary dendrite arms. Abstract: In the current work, T-joints consisting of 2.0 mm thick 2060-T8/2099-T83 aluminum-lithium alloys for aircraft fuselage panels have been fabricated by double-sided fiber laser beam welding with different filler wires. A new type wire CW3 (Al-6.2Cu-5.4Si) was studied and compared with conventional wire AA4047 (Al-12Si) mainly on microstructure and mechanical properties. It was found that the main combined function of Al-6.2%Cu-5.4%Si in CW3 resulted in considerable improvements especially on intergranular strength, hot cracking susceptibility and hoop tensile properties. Typical non-dendritic equiaxed zone (EQZ) was observed along welds' fusion boundary. Hot cracks and fractures during the load were always located within the EQZ, however, this typical zone could be restrained by CW3, effectively. Furthermore, changing of the main intergranular precipitated phase within the EQZ from T phase by AA4047 to T2 phase by CW3 also resulted in developments on microscopic intergranular reinforcement and macroscopic hoop tensile properties. In addition, bridging caused by richer substructure dendrites within CW3 weld's columnar zone resulted in much lower hot cracking susceptibility of the whole weld than AA4047.